2020
DOI: 10.1186/s12890-020-1058-5
|View full text |Cite
|
Sign up to set email alerts
|

Design for a multicenter, randomized, sham-controlled study to evaluate safety and efficacy after treatment with the Nuvaira® lung denervation system in subjects with chronic obstructive pulmonary disease (AIRFLOW-3)

Abstract: Background: Targeted lung denervation (TLD) is a bronchoscopically delivered ablation therapy that selectively interrupts pulmonary parasympathetic nerve signaling. The procedure has the potential to alter airway smooth muscle tone and reactivity, decrease mucous secretion, and reduce airway inflammation and reflex airway hyperresponsiveness. Secondary outcome analysis of a previous randomized, sham-controlled trial showed a reduction in moderate-to-severe exacerbations in patients with COPD after TLD treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…The absence of decline three years post-treatment compared with baseline supports stability for lung function and quality of life in this study and both are consistent with the stable rate of exacerbations observed in this study [24]. These observations will need to be con rmed in an ongoing large scale sham-controlled randomized trial (AIRFLOW-3) comparing the e cacy of TLD plus optimal medical care for patients with moderate-to-severe COPD against optimal medical care for COPD [25].…”
Section: Discussionsupporting
confidence: 82%
“…The absence of decline three years post-treatment compared with baseline supports stability for lung function and quality of life in this study and both are consistent with the stable rate of exacerbations observed in this study [24]. These observations will need to be con rmed in an ongoing large scale sham-controlled randomized trial (AIRFLOW-3) comparing the e cacy of TLD plus optimal medical care for patients with moderate-to-severe COPD against optimal medical care for COPD [25].…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, a control group is lacking with information on the actual decline in lung function over time in this specific patient group. Currently a large clinical trial with 5 year follow up is underway (Airflow-3, NCT03639051) [4] which has the potential to confirm our results.…”
supporting
confidence: 66%
“…The absence of decline three years post-treatment compared with baseline supports stability for lung function and quality of life in this study and both are consistent with the stable rate of exacerbations observed in this study [ 24 ]. These observations will need to be confirmed in an ongoing large scale sham-controlled randomized trial (AIRFLOW-3) comparing the efficacy of TLD plus optimal medical care for patients with moderate-to-severe COPD against optimal medical care for COPD [ 25 ].…”
Section: Discussionmentioning
confidence: 99%